Data-Driven Recommendations for Promoting Collaboration Among School Security Personnel and School Social Workers in the United States - Soohyoung Lee; Matthew Cuellar (International Journal of School Social Work, 2019)
In response to recent incidents of school violence in the United States over the last two decades, there has been a nationwide increase in the use of school security personnel in today’s schools. Concurrently, school social work practice continues to grow as a subspecialty of social work that provides crucial services to youth in school. Despite this increase in demand across both fields of practice, and an overlap in professional interests, current research suggests that we know little about how school social workers interact with and perceive school security personnel within their schools, and ultimately how such interaction and collaboration among professionals might influence school safety. This study aims to address this gap in the literature by exploring survey responses from a nation-wide sample of school social workers who report working in schools with different types of security personnel (n = 151). Findings suggest that increased interaction and positive perceptions of school security personnel are positively associated with perceived overall safety in school. Additionally, qualitative responses suggest a considerable percentage of school social workers feel that school security personnel might benefit from additional training and increased accessibility and collaboration. The purpose of this paper is to provide timely implications for school policing using the perspective of school social workers with the goal of promoting safety and collaboration in schools.
Keywords: School safety; school social work; social work practice; school security personnel